2020
DOI: 10.1186/s12995-020-00287-8
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of medical students’ proficiency regarding the hazards of radiological examinations on the health of workers and patients: a cross-sectional study from Palestine

Abstract: Background The use of radiological examination is increasing worldwide. Since radiation exposure can result in many health hazards, medical professionals, as well as medical students, should possess adequate knowledge regarding radiation and its related hazards to protect themselves and the patients. Many studies have assessed medical students’ knowledge on this topic, but never in Palestine. In this study, we aimed to examine Palestinian medical students’ awareness and knowledge regarding radiological examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…In a Palestinian based study, Awadghanem et al [12] noted that male participants achieved a higher score in general radiology knowledge assessment when compared to female participants (P 0.034). This is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a Palestinian based study, Awadghanem et al [12] noted that male participants achieved a higher score in general radiology knowledge assessment when compared to female participants (P 0.034). This is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 98%
“…Probably male students were encouraged to pursue a career in Radiology than their female counterparts were and this encouragement likely heightened the interest of males to learn more during the posting. [12] Vinod et al [9] observed that male undergraduate students who showed fondness for Radiology were 75 in number compared to 25 female students. They had the notion that this was probably because there were more male entrants into most medical schools than females.…”
Section: Discussionmentioning
confidence: 99%
“…Sima et al (2017) illustrated that radiation workers who had worked for longer years may have good experience and would likely practice safety precautionary measures. Recently, Cha et al (2020) and Awadghanem et al (2020) both studies reported that radiation workers who have over 8 years of work experience been more likely to show signs of health issues if he/she had not been complying with safety protocols during work proceedings. Dehghani et al (2014) added that job experience does matter mostly with safety awareness and utilization of protective equipment in the health facility.…”
Section: Work Experience and Safety Practicesmentioning
confidence: 99%
“…More detailed information is provided by CT scans than by standard X-ray examinations [ 3 ]. The use of CT scans has increased to 70 million scans per year since 1993 in the US [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…More detailed information is provided by CT scans than by standard X-ray examinations [3]. The use of CT scans has increased to 70 million scans per year since 1993 in the US [4]. However, while these radiologic tests are helpful in the diagnosis and treatment of patients, there are certain drawbacks as well.…”
Section: Introductionmentioning
confidence: 99%